2022
DOI: 10.1186/s12935-022-02787-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix stiffness mediates radiosensitivity in a 3D nasopharyngeal carcinoma model

Abstract: Purpose Radiotherapy is one of the essential treatment modalities for nasopharyngeal carcinoma (NPC), however, radioresistance still poses challenges. Three-dimensional (3D) tumor culture models mimic the in vivo growth conditions of cells more accurately than 2D models. This study is to compare the tumor biological behaviors of NPC cells in 2D, On-Surface 3D and Embedded 3D systems, and to investigate the correlation between radioresistance and extracellular matrix (ECM) stiffness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Previously, the correlation between CAFs and ECM was established in a study that observed the signature of CAF in the TME and defined the function of CAF based on gene expression and immunostaining ( Lee et al, 2020 ). Moreover, ECM remodeling has also been linked to tumor treatment resistance in several studies ( Drain et al, 2021 ; Pietilä et al, 2021 ; Fang et al, 2022 ). In our work, we explored five clusters of CAF subpopulations that presented potential interactions with important microbes, in which clusters 7 and 10 were found to be responsible for ECM formation, similar to another study reporting that microbiota inside CRC was co-localized with CAFs, activated the TLR2/NF-κB pathway in the CRC microenvironment ( Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the correlation between CAFs and ECM was established in a study that observed the signature of CAF in the TME and defined the function of CAF based on gene expression and immunostaining ( Lee et al, 2020 ). Moreover, ECM remodeling has also been linked to tumor treatment resistance in several studies ( Drain et al, 2021 ; Pietilä et al, 2021 ; Fang et al, 2022 ). In our work, we explored five clusters of CAF subpopulations that presented potential interactions with important microbes, in which clusters 7 and 10 were found to be responsible for ECM formation, similar to another study reporting that microbiota inside CRC was co-localized with CAFs, activated the TLR2/NF-κB pathway in the CRC microenvironment ( Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence has accumulated in recent years indicating a difference in radiosensitivity between cells growing in a 2D or 3D environment, and the majority of these studies have shown an increase in radioresistance in 3D cultures [ 15 , 24 , 33 , 34 ]. This is reflected in differences, which can be very significant, between survival curves obtained from 2D or 3D models [ 35 , 36 ]. For this reason, the exclusive use of 2D cellular models for the definition of survival curves and the application of the LQ model to radiotherapy plans could lead to an underestimation of the radiation dose necessary to eradicate the tumor and to an incorrect assessment of the risk–benefit ratio.…”
Section: The Linear–quadratic Model and The Implications Of Cellular ...mentioning
confidence: 99%
“…Stiffness increase in tumors has been shown to be fundamental in the regulation of many biological effects [ 9 , 29 , 36 , 70 , 77 , 81 ]. In particular, it has been reported that ECM stiffness can modulate the DNA damage response to radiation due to the ability of integrins to detect mechanical stimuli.…”
Section: Radioresistance Mechanisms In 3d Cell Modelsmentioning
confidence: 99%